Reduction of COD in Nam Son landfill leachate by electro-fenton as secondary treatment after electrocoagulation pretreatment - Son, Le Thanh; Khai, Le Cao (Vietnam Journal of Science and Technology, 2019)
Landfill leachate is a high-strength wastewater that is most difficult to deal with because the fluctuating of composition and quality as well as high concentration of specific pollutants (PAH, PCBs, heavy metals) and very high ammonia nitrogen and COD concentrations. So, after a pre-treatment as electrocoagulation, over 73% of COD has been treated from Nam Son landfill leachate, however the output value of COD still exceeds the QCVN 40:2011/BTNMT, column B. So, an electro-fenton process was employed to secondarily treat Nam Son landfill leachate, after an electrocoagulation pre-treatment. This electro-fenton system used a Pt gauze anode and a commercial carbon felt cathode to electrogenerate in situ hydrogen peroxide and regenerate ferrous ion as catalyst. In this study, the effects of various operating conditions such as initial pH, concentration of Fe2+ catalyst, current applied on reduction of COD in Nam Son landfill leachate were examined. At the optimal condition: applied current of 1A, pH 3, Fe2+ concentration of 0.1m M, Na2SO4 concentration of 0.05 M, 77.2% COD reduction can be reached within 60 min and the output value of COD is 130.9 mg.L-1, according to QCVN 40:2011/BTNMT, column B. The research results indicated that electro-fenton process can promise as a potential method in practice for secondary treatment of landfill leachate.